1991
DOI: 10.1203/00006450-199104000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Development of Circadian Sleep-Wake Rhythms in Preterm and Full-Term Infants

Abstract: ABSTRACT. We have compared the roles of neurologic maturity and environmental time cues in the development of the entrained circadian sleep-wake rhythm in the preterm and term human infant. The preterm infants (n = 19) spent some time after birth in a hospital nursery with no environmental time cues, whereas the term infants (n = 22) were exposed from birth to a cyclical light and dark environment with one major caregiver. The circadian sleepwake rhythm in the preterm infants entrained after a similar time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 8 publications
(11 reference statements)
3
37
1
1
Order By: Relevance
“…Second, human preterm infants were able to entrain the circadian clock by exposure to low-intensity cycled lighting (Rivkees, 2003;Rivkees et al, 2004). When comparing term and preterm infant circadian entrainment, the length of exposure to a cyclical light-dark environment was more important than neurologic maturity (McMillen et al, 1991). Third, the timing of the association found in this study, over the first 3 months of life, is consistent with prior reports of the progressive development of the circadian system in humans.…”
Section: Discussionsupporting
confidence: 86%
“…Second, human preterm infants were able to entrain the circadian clock by exposure to low-intensity cycled lighting (Rivkees, 2003;Rivkees et al, 2004). When comparing term and preterm infant circadian entrainment, the length of exposure to a cyclical light-dark environment was more important than neurologic maturity (McMillen et al, 1991). Third, the timing of the association found in this study, over the first 3 months of life, is consistent with prior reports of the progressive development of the circadian system in humans.…”
Section: Discussionsupporting
confidence: 86%
“…In support of our data, McMillen et al (23) also found the circadian rhythm of sleep in the preterm infants similar to term infants entrained after 6 to 10 wk of exposure to the home environment. However, because preterm infants were discharged home at approximately 35 wk PCA in their study, the entrainment to light-dark cycle took place at a significantly earlier PCA (47 wk) in these infants compared with the term group (49 wk).…”
Section: Discussionsupporting
confidence: 80%
“…The onset of the circadian rhythm of sleep was detected from 8 postnatal weeks in this preterm group. This age is similar to those previously reported for preterm (9.8 ± 2 weeks) and term (8.7 ± 2.7 weeks) babies (8). There was a parallelism between the appearance of such rhythm and the mean age at the onset of the salivary cortisol circadian rhythm.…”
Section: Circadian Rhythm Ontogenysupporting
confidence: 78%
“…In addition, this in-formation is not available for premature infants. The ontogenetic maturation of the circadian sleep-wake rhythms in preterm and full-term infants has been widely accepted as the result of the length of exposure to environmental time cues, rather than neurologic maturity (7)(8)(9). These observations prompted us to compare the effects of prematurity on the temporal evolution of the circadian variation in salivary cortisol and on the daily rhythm of sleep and wakefulness in preterm infants.…”
Section: Introductionmentioning
confidence: 99%